2009
DOI: 10.3389/neuro.09.070.2009
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological distinction between schizophrenia and schizoaffective disorder

Abstract: Schizoaffective disorder (SA) is distinguished from schizophrenia (SZ) based on the presence of prominent mood symptoms over the illness course. Despite this clinical distinction, SA and SZ patients are often combined in research studies, in part because data supporting a distinct pathophysiological boundary between the disorders are lacking. Indeed, few studies have addressed whether neurobiological abnormalities associated with SZ, such as the widely replicated reduction and delay of the P300 event-related p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 48 publications
0
33
0
1
Order By: Relevance
“…We assessed the transient GBR elicited by the standard tones presented as part of a three-stimulus auditory oddball task, described in more detail elsewhere (Ford et al, 2008, Mathalon et al, 2010). The high probability (p=.7) standard stimuli were 500Hz, 50 ms tones presented with a stimulus-onset asynchrony of 1.25 sec 210 times over the course of the task.…”
Section: Methodsmentioning
confidence: 99%
“…We assessed the transient GBR elicited by the standard tones presented as part of a three-stimulus auditory oddball task, described in more detail elsewhere (Ford et al, 2008, Mathalon et al, 2010). The high probability (p=.7) standard stimuli were 500Hz, 50 ms tones presented with a stimulus-onset asynchrony of 1.25 sec 210 times over the course of the task.…”
Section: Methodsmentioning
confidence: 99%
“…All EEG processing was performed as described previously (Mathalon et al, 2010). Briefly, EEG data from 3 midline sites (Fz, Cz and Pz) were analyzed.…”
Section: Erp Analysesmentioning
confidence: 99%
“…Amplitude decrease has been shown in chronic schizophrenia patients (Devrim-Ucok et al, 2006; Mathalon et al, 2010) and in clinical high risk (Jahshan et al, 2012; Mondragon-Maya et al, 2013). In recent onset subjects, amplitude deficits ( Valkonen-Korhonen et al, 2003b; Hermens et al, 2010; Kaur et al, 2011; Jahshan et al, 2012), but also a lack of them, have been reported (Frodl et al, 2001b; Devrim-Ucok et al, 2006; Atkinson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%